A narrativa jornalística imediata e tardia do desastre socioambiental na Região Serrana do Rio de Janeiro em 2011 - Huberty, Daniela Silva (2020)
This dissertation seeks to understand how the journalistic narrative about the socio-environmental disaster of 2011 in the mountainous region of Rio de Janeiro is transformed over time inside the journalistic coverage of the UOL news portal, based on the comparison between the news that is part of its immediate narrative and those published over a wide time frame. For this, it is theoretically and methodologically based on Narratology and, more specifically, on the Critical Narrative Analysis proposed by Motta (2013). Theoretically, the study apprehends the disaster as an event (QUÉRÉ, 2005) and discusses the need to understand it from a sociological point of view that allows the journalistic narrative to go beyond the “day of disaster” (VALENCIO, 2012) so that issues such as prevention and risk reduction can be problematized. The research corpus is formed by the selection of 58 news items released from January 12, 2011 to January 11, 2016, referring to the first 24, 48 and 72 hours of the disaster, one month, and those alluding to the ephemeris, when it celebrates one, two and five years. From the reconstruction of the narrative through the construction of a timeline of the event, and the decomposition and recomposition of its intrigue, we identified the elements that stood out in each of its episodes and the consequent change in the way of narrating over time. It was concluded that the narrative was built around the consequences of the disaster: the immediate narrative privileged factual information, through the constant updating of data and the search for characters linked to the government and institutions, while the late narrative started from a testimonial and emotional discourse in which the victims were protagonists.